Replacement of Highly Conserved E222 by the Photostable Non‐photoconvertible Histidine in GFP. Issue 10 (11th June 2014) - Auerbach, Dagmar; Klein, Martin; Franz, Silke; Carius, Yvonne; Lancaster, C. Roy D.; Jung, Gregor
Abstract The widely used green fluorescent protein (GFP) decarboxylates upon irradiation; this involves removal of the acidic function of the glutamic acid at position 222, thereby resulting in the irreversible photoconversion of GFP. To suppress this phenomenon, the photostable, non‐photoconvertible histidine was introduced at position 222 in GFP. The variant E222H shows negligible photodynamic processes and high expression yield. In addition, the stable and bright fluorescence over a wide pH range makes the E222H protein an alternative for GFP in fluorescence imaging and spectroscopy. Other fluorescent proteins are predicted to benefit from replacement of the catalytic glutamic acid by histidine.